Correlation between surgical success rate and severity of congenital glaucoma. Issue 4 (17th March 2005) - Al-Hazmi, A; Awad, A; Zwaan, J; Al-Mesfer, S A; Al-Jadaan, I; Al-Mohammed, A
Abstract : Aim: To study the correlation between severity of primary congenital glaucoma (PCG) and success of three types of surgery. Methods: This was a retrospective review of all records of patients diagnosed with PCG up to age 1 year who underwent goniotomy, trabeculotomy, or combined trabeculotomy-trabeculectomy with mitomycin C as initial procedure between 1982 and 2002 at the King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia. 532 paediatric glaucoma patients below age 1 year (820 eyes) with a minimum 1 year follow up were identified. The main outcome measures used for the surgeries were postoperative intraocular pressure, stability of the corneal diameter, and maintenance of corneal clarity. Surgical success was defined as a postoperative intraocular pressure of ⩽21 mm Hg without additional medical or surgical therapy, and with decreased corneal oedema, stabilised corneal diameter, and no additional optic nerve damage for at least 1 year after surgery. Complications, time of surgical failure, and follow up were recorded. Results: The eyes were grouped into mild (249), moderate (342), and severe (229) PCG, based on intraocular pressure, corneal diameter, and clarity. All three surgical procedures resulted in high success rates of 81–100% for the mild form of PCG. Eyes classified with moderate glaucoma had a 13%, 40%, and 80% success rate respectively for goniotomy, trabeculotomy, and combined trabeculotomy-trabeculectomy with mitomycin C. The success rate for severe PCG was 10% and 70% for trabeculotomy and combined surgery respectively. Goniotomy was never done for eyes with this condition. Conclusion: Clinical classification of PCG is helpful for surgical decision making. The mild form has a high surgical success regardless of the procedure chosen. Combined trabeculotomy-trabeculectomy with mitomycin C gave the best results for moderate and severe cases of PCG.